ANALISIS PENGUJIAN IMPAK METODA IZOD DAN CHARPY MENGGUNAKAN BENDA UJI ALUMUNIUM DAN BAJA ST37 - Chaerul Umam Wardani; Yudi Samantha; Haris Budiman (PROCEEDING STIMA)
Impact test intended to knowing the toughness of metal, as a result of sudden in a type temperature condition. Toughness is a measure of the energy require to break the material. This impact test tool here in after tested for the testing of aluminium and steel ST37. Before being tested spesimen aluminium and steel ST37 same, will be tested by the method charpy impact on test equipment certified Komite Akreditasi Nasional (KAN) and Japans Industrial Standard (JIS) in Balai Besar Bahan dan Barang Teknik ( B4T ) Bandung as a comparison of the outcome of the draft impact test equipment. Results of impact testing conducted in Balai Besar Bahan dan Barang Teknik (B4T) Bandung with test performed in laboratory material University Majalengka the prices of different impact but fracture of aluminium and steel ST 37 the same outcome. While the test results for Izod method on steel ST37 only performed in laboratory material University of Majalengka doesn't fracture. Because there are several factors in the test equipment and the test object is not testing criteria Izod method.Keyword: Testing, comparison, analys